Maternal cardiovascular function: longitudinal changes prior to and in pregnancy. (18th April 2012) - Mahendru, AA; Everett, TR; McEniery, CM; Wilkinson, IB; Lees, CC
Abstract : Normal pregnancy is associated with profound changes in maternal heart rate (HR), peripheral blood pressure (BP) and cardiac output (CO) as early as 5-6 weeks. However, longitudinal changes in central BP, pulse wave reflection and aortic stiffness during pregnancy beginning from pre-pregnancy have not been described. Our aim was to assess changes in maternal cardiovascular function, including measurements of wave reflections and aortic stiffness before, and during pregnancy- in early first trimester, second and third trimester. In this longitudinal study of 143 women planning to conceive (age: 27-38yrs), brachial and central BP, augmentation index (AIx), aortic pulse wave velocity (aPWV) and CO were assessed pre-pregnancy and repeated 2-3 weeks after the first positive pregnancy test, at 20-24weeks, 31-34weeks in 35 women who became pregnant. While HR ( P =0.001) increased significantly throughout pregnancy, both brachial and central BP reduced ( P <0.001). However, significant reduction in BP was seen very early in pregnancy compared to late pregnancy. AIx reduced significantly in early pregnancy ( P =0.001) with no further change by second trimester, followed by a significant increase in third trimester ( P =0.004). aPWV was unaltered in early pregnancy but reduced by second trimester ( P <0.001). This is the first study to investigate longitudinal changes in pulse wave reflection and aortic stiffness from pre-pregnancy. We have demonstrated profound changes in brachial, central BP and AIx very early in pregnancy. Furthermore, late first trimester data cannot be used as 'baseline' in order to identify the extent of cardiovascular adaptation in pregnancy as has been hitherto assumed.